Los ciclos productivos de Pinus taeda y su relación con el contenido de carbono orgánico del suelo en Misiones (Argentina) = Productive cycles of Pinus taeda and its relationship with organic carbon soil content in Misiones (Argentina) - Pahr, Norberto Manuel; Von Wallis, Alejandra; Aquino, Diego Rolando; Knebel, Otto Eduardo; Ferruchi, Maria Rosana (Facultad de Ciencias Forestales, Universidad Nacional de Misiones (UNaM) y EEA Montecarlo, INTA, 2024)
All forest cultivation requires a series of activities throughout its cycle. Some, such as harvesting, thinning and land preparation, generate important changes in site conditions, which motivates their monitoring through indicators. The organic matter soil content, through the variable easily oxidizable organic carbon (COfo), is considered an appropriate indicator attribute for its evaluation, because is sensitivity and importance in the change of soil properties. With this purpose, a study was carried out that covered different situations of Pinus taeda plantations in Misiones.